The association of nationwide trainee doctor mass resignations in South Korea with hospital utilization, expenditure, and patient outcomes - Kim, Seonghoon; Ahn, SangNam; Koh, Kanghyock; Lee, Donghyoun (Frontiers in Public Health, 2025)
In February 2024, over 90% of trainee doctors in South Korea’s teaching hospitals resigned en masse, severely disrupting healthcare delivery. We evaluated the associations of this mass resignation with hospital admission and length of stay, expenditure, and patients’ health outcomes in a tertiary teaching hospital. We analyzed inpatient claims data from Jeju National University Hospital (August 2022–July 2024), encompassing 40,577 hospital episodes. Using a difference-in-differences method, we compared outcomes 6 months before and after the mass resignation (February–July 2024 vs. August 2023–January 2024) against the same period 1 year earlier (February–July 2023 vs. August 2022–January 2023) to account for seasonal trends. Primary outcomes included daily hospital admissions, length of stay, total medical costs, 30-day readmission rates, and in-hospital mortality. Analyses were stratified by comorbidity burden using the Charlson Comorbidity Index. The mass resignation was associated with reduced daily hospital admissions (−9.45; 95% CI: −16.1 to −2.77; p = 0.01), decreased length of stay (−1.01 days; 95% CI: −1.97 to −0.06; p = 0.04), and lower healthcare expenditure (−40%; 95% CI: −68% to −12%; p = 0.01). No significant changes were observed in 30-day readmission rates or in-hospital mortality in the overall sample. However, among patients with higher comorbidity burden (CCI ≥ 1), 30-day readmission rates decreased significantly (−0.05; 95% CI: −0.14 to 0.04; p = 0.01). Despite no observed short-term mortality increases, reduced utilization among high-comorbidity patients raises concerns about care access during the crisis. The findings suggest that hospitals exhibited short-term adaptive capacity under workforce shortages, while reduced utilization among high-comorbidity patients raises concern for care access. Strengthening contingency planning, flexible staffing, and real-time monitoring systems will be critical to sustaining care quality during future disruptions. Long-term implications of sustained healthcare disruption warrant further investigation.